Tissue specific responses to cadmium-based quantum dots in the marine mussel Mytilus galloprovincialis - Lopes Rocha, Thiago (2020)
In recent years, Cd-based quantum dots (QDs) have generated interest from the life sciences community due to their potential applications in nanomedicine, biology and electronics. However, these engineered nanomaterials can be released into the marine environment, where their environmental health hazards remain unclear. This study investigated the tissue-specific responses related to alterations in the antioxidant defense system induced by CdTe QDs, in comparison with its dissolved counterpart, using the marine mussel Mytilus galloprovincialis. Mussels were exposed to CdTe QDs and dissolved Cd for 14 days at 10 μgCd L(-1) and biomarkers of oxidative stress [superoxide dismutase (SOD), catalase (CAT), glutathione peroxidases (total, Se-independent and Se-dependent GPx) and glutathione-S-transferase (GST) activities] were analyzed along with Cd accumulation in the gills and digestive gland of mussels. Results show that both Cd forms changed mussels' antioxidant responses with distinct modes of action (MoA). There were tissue- and time-dependent differences in the biochemical responses to each Cd form, wherein QDs are more pro-oxidant when compared to dissolved Cd. The gills are the main tissue affected by QDs, with effects related to the increase of SOD, GST and GPx activities, while those of dissolved Cd was associated to the increase of CAT activity, Cd accumulation and exposure time. Digestive gland is a main tissue for accumulation of both Cd forms, but changes in antioxidant enzyme activities are smaller than in gills. A multivariate analysis revealed that the antioxidant patterns are tissue dependent, indicating nano-specific effects possibly associated to oxidative stress and changes in redox homeostasis.